THE EFFECT OF PRICE, PROMOTION AND QUALITY OF MAXIM APPLICATION SERVICES ON CUSTOMER SATISFACTION IN MEDAN CITY - Reja Filif Andrian; Ratna Oktavia Situmorang; Tri Putri Enjelina Grasela Sinabang; Holfian Daulat Tambun Saribu; Rintan Saragih (ZILLZELL MEDIA PRIMA, 2026)
This study examines the effect of price, promotion, and service quality on customer satisfaction with the Maxim application in Medan City. The rapid growth of online transportation services has encouraged service providers to strengthen marketing strategies that can improve customer satisfaction and maintain competitiveness. This research used a quantitative approach with an explanatory research design. Primary data were collected through questionnaires distributed to 100 active Maxim users in Medan City. The data were analyzed using validity and reliability tests, classical assumption tests, and multiple linear regression analysis. The results show that price has a positive and significant effect on customer satisfaction, with a significance value of 0.008. Promotion also has a positive and significant effect, with a significance value of 0.000, and becomes the most dominant variable in influencing customer satisfaction. However, service quality does not have a significant partial effect, with a significance value of 0.857. Simultaneously, price, promotion, and service quality have a significant effect on customer satisfaction, as indicated by an F-value of 41.960 and a significance value of 0.000. The Adjusted R Square value of 0.554 indicates that the three variables explain 55.4% of the variation in customer satisfaction. These findings suggest that Maxim should maintain competitive pricing, strengthen promotional strategies, and improve service consistency to build sustainable customer satisfaction.